Can ultra-poverty be sustainably improved? Evidence from BRAC in Bangladesh - Raza, Wameq A.; Das, Narayan Chandra; Misha, Farzana A. (Taylor & Francis, 2022)
This article was published in The Journal of Development Effectiveness [©2012 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/19439342.2012.686046 The Article's website is at: https://www.tandfonline.com/doi/abs/10.1080/19439342.2012.686046